Tolling the Bell for "Too-Big-to-Fail"? – A Comparison Between Four Special Bank Resolution Regimes - Yoichi Iwasa; Uwe Vollmer (Credit and Capital Markets – Kredit und Kapital, 2017)
In many countries, legislators have introduced special bank resolution regimes in order to handle the "too-big-to-fail"-(TBTF)-problem. Bank resolution schemes allow supervisors to restructure or liquidate an ailing bank, even without the consent of the bank owners. We identify key elements of bank resolution schemes and consider how they are implemented in Japan, the US, the Euro area, and in the UK. We compare the bank resolution regimes in these countries and evaluate whether they comply with the "Key Attributes" proposed by the Financial Stability Board. We also ask whether they are effective in addressing the TBTF-problem and promoting financial stability. – – Das Ende von "Too-Big-to-Fail"? – Ein Vergleich zwischen vier Bankabwicklungsregimen In vielen Ländern hat der Gesetzgeber spezielle Abwicklungsinstrumente für Banken geschaffen, um das "Too-big-to-fail"-(TBTF)-Problem zu lösen. Diese Instrumente erlauben es der Bankenaufsicht, in finanzielle Schwierigkeiten geratenen Banken zu sanieren oder zu liquidieren – auch ohne Zustimmung der Eigentümer. Wir identifizieren Kernelemente von Bankenabwicklungsregimen und prüfen, wie diese umgesetzt wurden in Japan, den USA, der Eurozone und in Großbritannien. Wir vergleichen die in diesen Ländern bestehenden Bankenabwicklungsregime und fragen, inwieweit sie den "Key Attributes" genügen, die vom Financial Stability Board vorgegeben wurden. Wir fragen auch, inwieweit die nationalen Abwicklungsregime das TBTF-Problem lösen und zur finanziellen Stabilität beitragen können.
Keywords: G38; G01; G21; 330; Bank resolution; too-big-to-fail; statutory bail-in; bank levy; resolution fund; single-point-of-entry; multiple-point-of-entry